2017
DOI: 10.1186/s12884-017-1620-1
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous first trimester miscarriage rates per woman among parous women with 1 or more pregnancies of 24 weeks or more

Abstract: BackgroundThe purpose of this study was to quantify spontaneous first trimester miscarriage rates per woman among parous women. A vast amount of data has accumulated regarding miscarriage rates per recognized pregnancy as well as about recurrent miscarriage. This is the second study of miscarriage rates per woman in a parous population and the first study of recurrent and non-recurrent, spontaneous first trimester miscarriage rates per woman in a large parous population.MethodsExtraction of the following varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
57
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 18 publications
9
57
3
2
Order By: Relevance
“…We assessed the potential genetic overlap between miscarriage phenotypes and other traits and found significant (Bonferroni corrected significance level 0.05/72=6.9×10 -4 ) genetic correlations between European-ancestry sporadic miscarriage analysis and number of children (rg=0.69, se=0.12, P= 7.2×10 -9 ) and age at first birth (rg=-0.40, se=0.10, P=3.3×10 -5 )(Supplementary Table 6). The positive genetic correlation between sporadic miscarriage and number of children is consistent with observational associations between sporadic miscarriage and greater number of live births 27 .…”
supporting
confidence: 85%
See 1 more Smart Citation
“…We assessed the potential genetic overlap between miscarriage phenotypes and other traits and found significant (Bonferroni corrected significance level 0.05/72=6.9×10 -4 ) genetic correlations between European-ancestry sporadic miscarriage analysis and number of children (rg=0.69, se=0.12, P= 7.2×10 -9 ) and age at first birth (rg=-0.40, se=0.10, P=3.3×10 -5 )(Supplementary Table 6). The positive genetic correlation between sporadic miscarriage and number of children is consistent with observational associations between sporadic miscarriage and greater number of live births 27 .…”
supporting
confidence: 85%
“…We focused only on outcomes with at least one observation among the cases, resulting in testing >6,000 ICD codes for sporadic and >1,000 ICD codes for recurrent miscarriage. For sporadic miscarriage, the majority of associations were related to pregnancy, childbirth and the puerperium (P-values ranging between 9.9×10 -79 and 4.4×10 -2 ; Supplementary Table 7), supporting the observation that having more live births is associated with miscarriage 27 . Sporadic miscarriage was also positively associated with a wide variety of diagnoses, including asthma (P=1.6×10 -20 , OR=1.2 (1.19-1.3)), stillbirth (P=5.1×10 -5 , OR=74.3 (10.0-549.2)), depressive episodes (P=1.4×10 -7 , OR=1.…”
supporting
confidence: 58%
“…Recurrent pregnancy loss (RPL), defined as two pregnancy losses prior to 20 weeks from the last menstrual period, occurs in 1-3% of all couples trying to conceive (ESHRE, 2017). Based on available data, there is consensus that women should not undergo extensive evaluation after a single first trimester or early second trimester pregnancy loss, given that these are relatively common and sporadic events with only a modestly increased risk of recurrence (Knudsen et al, 1991;Nybo Andersen et al, 2000;Cohain et al, 2017). In prospective studies, the risk of pregnancy loss increases with each loss from approximately 11% amongst nulligravidae to approximately 40% after three or more losses (Magnus et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study conducted by Biesiada et al [ 20 ] that compared 41 women with first-trimester IUH and controls, they observed that IUH was more frequent among multiparous pregnant women than among women with low parity. The miscarriage rate increases with maternal age [ 21 ], parity [ 21 ], and the presence of IUH [ 7 ]. In our study, no other maternal characteristics or ultrasound parameters were found between the IUH and non-IUH groups.…”
Section: Discussionmentioning
confidence: 99%